Strategi Pengembangan Ekonomi Kreatif Berbasis Talenta Generasi Emas di Era Digital - Divani Akbar; Alifiana, Alifiana; Febrianti Dian Kusuma Wardani; Lutfia Hapsari; Shahibah Yuliani (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to identify the types of products or creative works produced by Indonesia’s golden generation in the context of developing a talent-based creative economy in the digital era. A talent-based economy refers to an economic model that leverages individual skills, creativity, and innovation as the main capital for generating economic value. Using a literature review approach, this research analyzes the implementation of a talent- driven creative economy, particularly how the youth especially Gen Z and millennials produce various digital outputs such as illustrations, animations, educational applications, video content, NFTs, and social media-based e-commerce products. This implementation reflects the integration of individual creativity with digital technology utilization, aligning with core 21st-century skills such as critical thinking, collaboration, communication, and digital literacy. The findings reveal that the creative economy contributes not only to cultural and artistic sectors but also to real economic sectors such as digital MSMEs, content industries, educational technology (edutech), and the broader digital economy. These insights show that with the support of digital infrastructure, technological literacy, and affirmative policies, the golden generation can foster innovation with economic value while enhancing national competitiveness amid global transformation toward Indonesia Emas 2045.